Grid-Based and Polytopic Linear Parameter-Varying Modeling of Aeroelastic Aircraft with Parametric Control Surface Design - Réka Dóra Mocsányi; Béla Takarics; Aditya Kotikalpudi; Bálint Vanek (Fluids, 2020)
The main direction of aircraft design today and in the future is to achieve more lightweight and higher aspect ratio airframes with the aim to improve performance and to reduce operating costs and harmful emissions. This promotes the development of flexible aircraft structures with enhanced aeroelastic behaviour. Increased aeroservoelastic (ASE) effects such as flutter can be addressed by active control technologies. Control design for flutter suppression heavily depends on the control surface sizing. Control surface sizing is traditionally done in an iterative process, in which the sizing is determined considering solely engineering rules and the control laws are designed afterwards. However, in the case of flexible vehicles, flexible dynamics and rigid body control surface sizing may become coupled. This coupling can make the iterative process lengthy and challenging. As a solution, a parametric control surface design approach can be applied, which includes limitations of control laws in the design process. For this a set of parametric models is derived in the early stage of the aircraft design. Therefore, the control surfaces can be optimized in a single step with the control design. The purpose of this paper is to describe as well as assess the developed control surface parameterized ASE models of the mini Multi Utility Technology Testbed (MUTT) flexible aircraft, designed at the University of Minnesota. The ASE model is constructed by integrating aerodynamics, structural dynamics and rigid body dynamics. In order to be utilized for control design, control oriented, low order linear parameter-varying (LPV) models are developed using the bottom-up modeling approach. Both grid- and polytopic parametric LPV models are obtained and assessed.